2024
DOI: 10.31235/osf.io/zkpb7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Private Hosting on the Integration of Ukrainian Refugees

Mathis Herpell,
Moritz Marbach,
Niklas Harder
et al.

Abstract: Amidst the Ukrainian displacement crisis, private hosting of refugees in Europe has surged, yet its impact on integration remains understudied. This research investigates the effects of private hosting on Ukrainian refugee integration in Germany. Utilizing data from one of the largest non-profit matching platforms for private refugee accommodation, we compare multidimensional integration outcomes of refugees matched with private hosts with observably similar refugees who applied for private hosting but were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Most host family arrangements are stable and stay in place for a long period (Strauss, Fuchs, and Ammann 2023); around half of the Ukrainian refugees who moved out of host families did so because they found their own accommodation. Host families are helpful for social integration and can help refugees with practical and administrative questions, and attempts to find paid work (Strauss, Fuchs, and Ammann 2023;Eser Davolio et al 2023;Ammann Dula et al 2024;Herpell et al 2024). Support for host families by officials varies a great deal by canton.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most host family arrangements are stable and stay in place for a long period (Strauss, Fuchs, and Ammann 2023); around half of the Ukrainian refugees who moved out of host families did so because they found their own accommodation. Host families are helpful for social integration and can help refugees with practical and administrative questions, and attempts to find paid work (Strauss, Fuchs, and Ammann 2023;Eser Davolio et al 2023;Ammann Dula et al 2024;Herpell et al 2024). Support for host families by officials varies a great deal by canton.…”
Section: Discussionmentioning
confidence: 99%
“…A large and systematic study in Germany found no effect of living with a host family and the ability to find paid work (Herpell et al 2024). While living with host families improves social integration and the ability to navigate everyday situations, language acquisition and economic integration do not appear to follow suit systematically (Herpell et al 2024).…”
Section: Job Visibilitymentioning
confidence: 99%
See 3 more Smart Citations